2020
DOI: 10.3390/antiox9111049
|View full text |Cite
|
Sign up to set email alerts
|

Nasally Administered Lactococcus lactis Secreting Heme Oxygenase-1 Attenuates Murine Emphysema

Abstract: Emphysema, a type of lung-destroying condition associated with chronic obstructive pulmonary disease (COPD), is an inflammatory lung disease mainly due to cigarette smoke exposure. As there is no curative therapy, prevention should be considered first by cessation of smoking to avoid exposure to oxidative stresses and inflammatory mediators. In addition, therapies involving antioxidative and/or anti-inflammatory agents such as heme oxygenase (HO)-1 are candidate treatments. We developed a new tool using geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…This L. Lactis vaccine is food grade and safer because it uses a lactose selection system and does not use antibiotics. L. lactis has been widely tested as a therapeutic career [10,11], including in vaccine delivery systems [7,12]. This microbe-based vaccine is highly suitable when administered via the intranasal and oral routes, which is in line with the results of this study.…”
Section: Discussionsupporting
confidence: 82%
“…This L. Lactis vaccine is food grade and safer because it uses a lactose selection system and does not use antibiotics. L. lactis has been widely tested as a therapeutic career [10,11], including in vaccine delivery systems [7,12]. This microbe-based vaccine is highly suitable when administered via the intranasal and oral routes, which is in line with the results of this study.…”
Section: Discussionsupporting
confidence: 82%
“…In terms of oxidative stress, Nrf2, as a nuclear transcription activator, regulated the induction of defensive genes encoding the detoxifying enzymes and antioxidant proteins [ 51 ]. HO-1 is a downstream protein of Nrf2, which showed protective effects against oxidative stress [ 52 ]. According to the previous reports, decreased expression of Nrf2 was observed in the lung of emphysema patients, while the therapeutic regimens that maintained or promoted the level of Nrf2 was potential therapy for emphysema [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, IL-1Ra was secreted in a much higher amount (2 mg/L) when compared with other cytokines in previous studies. The same plasmid was used in a pioneer study [ 148 ] that showed that recombinant L. lactis can be administered nasally in order to deliver therapeutical molecules to the lungs, and further into the systemic circulation.…”
Section: Plasmid Vectors Available For Plasmid Dna and Recombinantmentioning
confidence: 99%